Bibliometric Analysis of Erectile Dysfunction Publications in Urology and Sexual Medicine Journals. Issue 10 (12th September 2018) - Rezaee, Michael E.; Johnson, Heather A.; Munarriz, Ricardo M.; Gross, Martin S.
Abstract: Introduction: Scientific literature has experienced a significant growth in the number of authors per publication each year. Erectile dysfunction (ED) is one of the most common urologic conditions, accounting for over 2.9 million outpatient visits per year. Given the prevalence of ED and the large literature base available on this condition, bibliometric analysis of the ED literature could provide urologists and sexual medicine specialists with a better understanding of publication trends in this topic area. Aim: The purpose of this study was to investigate trends in authorship, citations, and impact score for ED original and review articles published in urology and sexual medicine journals. Methods: We analyzed ED original research and review articles indexed in MEDLINE between January 1, 2006, and December 31, 2016. Descriptive statistics were used to evaluate the mean number of authors for articles by journal type and time period (2006 vs 2016). Linear regression was used to examine the relationship between number of authors, number of citations, and relative citation ratio (RCR). Main Outcome Measure: The primary outcomes of interest included mean number of authors, citations, and RCR per manuscript by journal type and time period. Results: A total of 3, 516 articles were analyzed, 2, 938 (83.6%) original and 578 (16.4%) review articles. The mean number of authors among ED publications increased from 4.8 in 2006 to 6.4 in 2016, a 34.4% increase. Original articles had a greater mean number of authors compared to review articles (6.0 vs 4.3, P < .001). The mean number of authors for original articles significantly increased from 5.0 in 2006 to 7.0 in 2016 ( P < .001), an increase of 38.9%. A positive linear relationship was observed between mean number of authors and number of citations per manuscript (r = 0.015, P < .01) as well as RCR (r = 0.37, P < .0001). The largest authorship increases were observed in European Urology (78.8%), BJU International (78.6%), and Journal of Sexual Medicine (58.1%). Clinical Implications: Authorship trends should be taken into consideration when urologists and sexual medicine experts review ED articles for the purpose of informing patient care. Strength and Limitations: Primary strengths include a large literature base spanning multiple years for analysis and a systematic literature search to identify relevant ED literature. Findings are limited to ED literature published in the urology and sexual medicine journals analyzed. Conclusion: The number of authors per ED manuscript has significantly increased over time, most notably among original research articles. Increasing authorship was associated with more citations and higher RCR in the ED literature.